2008
DOI: 10.1007/s11408-008-0074-x
|View full text |Cite
|
Sign up to set email alerts
|

How do commodity futures respond to macroeconomic news?

Abstract: Commodities, Macroeconomic announcements, Business cycle, E44, G14,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 35 publications
5
32
0
1
Order By: Relevance
“…Both first-and second moment linkages are stronger in the post-September 2008 period. This is consistent with the evidence provided by previous studies that commodities such as gold are more sensitive to news releases during recessions, when there is greater uncertainty (see, e.g., Hess et al, 2008). Overall, our findings confirm that commodities, despite not being financial assets, respond to macro news (especially their volatility), and also suggest that the global financial crisis has strengthened such linkages.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both first-and second moment linkages are stronger in the post-September 2008 period. This is consistent with the evidence provided by previous studies that commodities such as gold are more sensitive to news releases during recessions, when there is greater uncertainty (see, e.g., Hess et al, 2008). Overall, our findings confirm that commodities, despite not being financial assets, respond to macro news (especially their volatility), and also suggest that the global financial crisis has strengthened such linkages.…”
Section: Discussionsupporting
confidence: 92%
“…Despite not being financial assets, the latter have been shown to be affected by variables such as interest rates (Frankel, 2008) and the US dollar exchange rate, both of which are known to respond to news announcements. Frankel and Hardouvelis (1985) provide evidence of a statistically significant response to US money supply announcements; effects of macro news on various commodity prices are also found by Cai et al (2001), Hess et al (2008), Kilian and Vega (2008); commodities futures prices have been reported to be affected as well (Barnhart, 1989;Ghura, 1990). Roache and Rossi (2010) in particular show that they are influenced by the surprise element in macro news, with evidence of a pro-cyclical bias after controlling for the effects of the US dollar, the only exception being gold, which reacts counter-cyclically given its role as a safe heaven and store of value, and is more sensitive to bad news and higher uncertainty.…”
Section: Introductionmentioning
confidence: 88%
“…McQueen and Roley (1993) note this effect in the U.S. stock market, while Cook and Korn (1991) and Roley and Sellon (1995) find the relationship for long-term rates varies over the business cycle as market participants alter their views on the persistence of monetary policy actions. Hess et al (2008) show that daily commodity prices are responsive only during recessionary periods.…”
Section: Introductionmentioning
confidence: 95%
“…In one of the early studies Goldman Sachs&Co. (1996) confirmed countercyclical movement of traditional investing assets and found commodities responding positively to current macroeconomic conditions. Hess et al (2008) focused their attention on a setof seventeen US macroeconomic announcements and its impact on commodity, equity and bond prices for the sample period 1989-2005. They analysed this relationship under two frameworks: unconditionally and conditionally on business cycle phase, however.…”
Section: Commodities and Business Cyclementioning
confidence: 99%